Distribution of Legionella pneumophila bacteria and Naegleria and Hartmannella amoebae in thermal saline baths used in balneotherapy - Żbikowska, Elżbieta (Springer-Verlag, 2012)
The present study was aimed at investigating the coexistence and interactions between free living amoebae of Naegleria and Hartmannella genera and pathogenic Legionella pneumophila bacteria in thermal saline baths used in balneotherapy in central Poland. Water samples were collected from November 2010 to May 2011 at intervals longer than 1 month. The microorganisms were detected with the use of a very sensitive fluorescence in situ hybridisation method. In addition, the morphology of the amoebae was studied. Despite relatively high salinity level, ranging from 1.5 to 5.0 %, L. pneumophila were found in all investigated baths, although their number never exceeded 10(6) cells dm(−3). Hartmannella were not detected, while Naegleria fowleri were found in one bath. The observation that N. fowleri and L. pneumophila may coexist in thermal saline baths is the first observation emphasising potential threat from these microorganisms in balneotherapy.